(untitled) - Lu, Henry C. (New York, 1991)
Classification of Chinese Herbs; The Chinese view of the causes of disease; How to decoct and take herbs; The Herbs and their legends....
Keywords: Herbs,Thảo mộc,Y học, Trung Quốc,Medicine, Chinese; Therapeutic use,Sử dụng trị liệu